![y'=(t+y)^2-1](https://img.qammunity.org/2021/formulas/mathematics/college/scqv7yxrl4vs7ggti8wvqwx3jk9n7h6zpg.png)
Substitute
, so that
, and
![u'=u^2-1](https://img.qammunity.org/2021/formulas/mathematics/college/jchnc6uyvinx96pokzdwgx1mlwgk9fj7jq.png)
which is separable as
![(u')/(u^2-1)=1](https://img.qammunity.org/2021/formulas/mathematics/college/rp01n93kzzjquhoxjng0clpbzwdd7ix2uh.png)
Integrate both sides with respect to
. For the integral on the left, first split into partial fractions:
![\frac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)=1](https://img.qammunity.org/2021/formulas/mathematics/college/cdw8znaf210c504ggehbtm55fziafhwwlu.png)
![\displaystyle\int\frac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)\,\mathrm dt=\int\mathrm dt](https://img.qammunity.org/2021/formulas/mathematics/college/ai2z2ppg9vkt4ottz2fht0deq8dor3w7ih.png)
![\frac12(\ln|u-1|-\ln|u+1|)=t+C](https://img.qammunity.org/2021/formulas/mathematics/college/tk45sw2lcarrl9tfif16c5fxzk90oyfo7w.png)
Solve for
:
![\frac12\ln\left|(u-1)/(u+1)\right|=t+C](https://img.qammunity.org/2021/formulas/mathematics/college/oc55evzw0wgdohsyc64wjvb9yvil49g9r0.png)
![\ln\left|1-\frac2{u+1}\right|=2t+C](https://img.qammunity.org/2021/formulas/mathematics/college/f4atgfcws6r74aavq9ld85ur0xlmpgovsm.png)
![1-\frac2{u+1}=e^(2t+C)=Ce^(2t)](https://img.qammunity.org/2021/formulas/mathematics/college/qdjt0de506d06n6ift0b2nurhguom7xrzv.png)
![\frac2{u+1}=1-Ce^(2t)](https://img.qammunity.org/2021/formulas/mathematics/college/q7dh150dbowre8inn8goz5vn1qw6o16ehr.png)
![\frac{u+1}2=\frac1{1-Ce^(2t)}](https://img.qammunity.org/2021/formulas/mathematics/college/owwwb3y2qei975ebskzzbal71sw7atww2u.png)
![u=\frac2{1-Ce^(2t)}-1](https://img.qammunity.org/2021/formulas/mathematics/college/w3irmfzuqwr8feeiq6rqe8p6lijr45tzg7.png)
Replace
and solve for
:
![t+y=\frac2{1-Ce^(2t)}-1](https://img.qammunity.org/2021/formulas/mathematics/college/8xzckm2d1e638qkzmucpemrq9mclnczm4k.png)
![y=\frac2{1-Ce^(2t)}-1-t](https://img.qammunity.org/2021/formulas/mathematics/college/y75h01fvfiwibs1h7vgbrcm4xellg3bj5z.png)
Now use the given initial condition to solve for
:
![y(3)=4\implies4=\frac2{1-Ce^6}-1-3\implies C=\frac3{4e^6}](https://img.qammunity.org/2021/formulas/mathematics/college/hhqkywi6chi1rd7hnd6c4kyy3ri1o0yr1j.png)
so that the particular solution is
![y=\frac2{1-\frac34e^(2t-6)}-1-t=\boxed{\frac8{4-3e^(2t-6)}-1-t}](https://img.qammunity.org/2021/formulas/mathematics/college/jvj4b8e3r4h9c5dmd03i93st90m8yli7ue.png)